Managing problem drinking of alcohol – screening and brief intervention - Hanwella, Raveen; De Silva, V.A. (Ceylon Medical Journal, 2009)
It is important to identify and manage problem drinking as it causes a significant burden of disease. There are simple screening procedures and management techniques which are effective in outpatient settings. All doctors should educate themselves and master these skills.
Keywords: drinking problem; alcohol